A survey on the information needs and uses of research staff and researchers at the Philippine Institute for Development Studies (PIDS) with implications for library collection development - Tolentino, Valentina V. (Institute of Library Science, University of the Philippines Diliman, 1986)
This study was conducted to determine the information needs of the research staff and researchers of the Philippine Institute for Development Studies (PIDS) and the implications of such needs to serve as a guide to collection development for the Institute's Library. It aimed to identify specific needs for information as well as the problems, purposes for which information is sought, the sources of information, subject areas and titles of periodicals for which the library must build its collection.